Machines of Sentient Resonance - Koutsomichalis, Marinos (My University, 2023)
A DIWO (do it with others) experiment where AI meets speculative design, sci-fi, and cyberpunk. Workshop participants will be asked to give flesh to illustrations of non-existent machines generated by a state-of-the-art AI text-to-image generation pipeline. AI responds to ‘machine of sentient resonance’ and other similar prompts with pictures of haphazard apparatuses that are subsequently made real by the students that are, additionally, required to come up with (real or fictional) functions/uses for/of them.